MCS-18, a natural product isolated from Helleborus purpurascens, inhibits maturation of dendritic cells in ApoE-deficient mice and prevents early atherosclerosis progression - Dietel, Barbara; Muench, Rabea; Kühn, Constanze; Kerek, Franz; Steinkasserer, Alexander; Achenbach, Stephan; Garlichs, Christoph; Zinser, Elisabeth (Atherosclerosis, 2014)
Inflammation accelerates both plaque progression and instability in the pathogenesis of atherosclerosis. The inhibition of dendritic cell (DC) maturation is a promising approach to suppress excessive inflammatory immune responses and has been shown to be protective in several autoimmune models. The aim of this study was to investigate the immune modulatory effects of the natural substance MCS-18, an inhibitor of DC maturation, regarding the progression of atherosclerosis in ApoE-deficient mice.ApoE-deficient mice were fed for twelve weeks with a Western-type diet (n = 32) or normal chow (control group; n = 16). Animals receiving high-fat diet were treated with MCS-18 (500 ?g/kg body weight, n = 16) or saline (n = 16) twice a week. After 12 weeks, animals were transcardially perfused and sacrificed. The percentage of mature DCs (CD3(-)/CD19(-)/CD14(-)/NK1.1(-)/CD11c(+)/MHCII(+)/CD83(+)/CD86(+)) and T cell subpopulations (CD4(+)/CD25(+)/Foxp3(+), CD3/CD4/CD8) was analyzed in peripheral blood and in the spleen using flow cytometry. Plaque size was determined in the aortic root and the thoracoabdominal aorta using en-face staining. Immunohistochemical stainings served to detect inflammatory cells in the aortic root. Several cytokines and chemokines were determined in serum using multiplex assays.In splenic cells derived from saline-treated atherosclerotic mice an increased DC maturation, reflected by the upregulation of CD83 and CD86 expression, was observed. The enhanced expression of both maturation markers was absent in MCS-18 treated atherosclerotic mice. While the percentage of splenic Foxp3 expressing Treg was increased in animals receiving MCS-18 compared to saline-treated atherosclerotic mice, cytotoxic T cells were reduced in the spleen and in atherosclerotic lesions of the aortic root. Furthermore, proatherogenic cytokines (e.g. IL-6 and IFN-?) and chemokines (e.g. MIP-1?) were decreased in serum of MCS-18-treated animals when compared to saline-treated atherosclerotic mice. Also plaque size in the aortic root and the thoracoabdominal aorta was significantly lower following administration of MCS-18.This study provides for the first time evidence that MCS-18 is able to prevent the onset of atherosclerosis in ApoE-deficient mice. The observed anti-atherogenic effect is associated with the suppression of DC maturation and an inhibited migration and proliferation of cytotoxic T cells.
EVALuna2:11981